Zur Verteilung der Laufkäfer in Feldmonokulturen (Coleoptera: Carabidae). - Skuhravý, Václav; Louda, J.; Sýkora, J. (Contributions to Entomology = Beiträge zur Entomologie, 1971)
A study of the distrubution of the ground beetles in field monocultures made in two localities brought the following results: The frequency of the occurrence of ground beetles in monocultures is greatly influenced by microclimatic conditions (density of plant growth, configuration of the ground). The ecological requirements of the species Pterostichus vulgaris, P. cupreus and Harpalus rufipes are very similar, while those of Bembidion lampros are different. It was observed that Pterostichus vulgaris frequently changes its habitat.